Traumatic Isolated Coracoid Fractures in the Adolescent - Amol R. Chitre; Hiren M. Divecha; Mounir Hakimi; Hans A. J. Marynissen (Case Reports in Orthopedics)
Coracoid fractures are rare injuries in themselves. Even rarer are isolated fractures of the coracoid in the skeletally immature patient. Due to the low numbers of these fractures, there is no true consensus on how to treat them. We report two cases of an isolated fracture of the coracoid. Case A is a 13-year-old boy who sustained the coracoid fracture following a skiing injury; case B is a 15-year-old boy who fell onto the right shoulder during a wheelbarrow race at school. Initial radiographs in case A suggested a displaced fracture; however, a CT scan taken after a short period of conservative treatment showed minimal displacement. In case B both the radiographs and CT scan showed no displacement. Both injuries were treated conservatively and united uneventfully with a full return to function. We advocate conservative management for these injuries in the skeletally immature patient.